(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
The article emphasizes that in Rumi’s works, spousal relationships should be based not on one-sided dominance, but on mutual respect and harmony. In his opinion, it is analyzed that the husband understands the heart of the wife, and the wife listens to the husband’s words from the heart - this is a guarantee of peace and prosperity in the family.